The Impact of Transit Oriented Development on Walkability: A Case Study of Dukuh Atas Station, Jakarta - Napitupulu, Deciana Matiur Ria; Rudiarto, Iwan (Jurnal Pembangunan Wilayah dan Kota, 2025)
Jakarta has one of the world's lowest averages daily step counts due to a variety of factors, including a changing urban environment and a lack of pedestrian infrastructure. In response, the Jakarta government shifted its development strategy to prioritize mass transportation and pedestrians over private vehicles. However, tackling relatively complicated urban issues cannot be accomplished solely by strengthening the transport system; it must be followed by urban development oriented towards transit locations. Therefore, "transit-oriented development" (TOD) has been introduced to increase the neighbourhood's walkability. Walkability is described as a key indicator of active travel or as a parameter of how useful the built environment is for people who walk to various locations and for multiple purposes.The Dukuh Atas TOD, one of Jakarta's earliest TODs, is used as a case study – focusing on a 400-meter-radius core area – to analyze how TOD intervention impacts the walkability of an area.The study used descriptive qualitative methods, including the production of maps at two different time periods to compare conditions before and after the construction of the MRT station and the Dukuh Atas TOD, conducting field observationsto directly observe and understand, capture phenomena that arise, record them, and consider the relationships between aspects of these events, and gathering pedestrian and commuter perceptionsthrough questionnaires and interviews to analyze the variables of intermodal conflict on the pathway, maintenance and cleanliness, connectivity, amenities, and disability infrastructure. According to the variables used in this study to determine whether TOD intervention has affected walkability in Dukuh Atas area, despite some of sidewalks are still inaccessible to everyone, the results indicate that several government interventions implemented of Dukuh Atas TOD development have significantly improved walkability in several zones. This research is expected to contribute to the improvement of Dukuh Atas TOD in creating a walkable environment.